Detailed Environmental Analysis Concerning a Proposed Liquefied Natural Gas Facility for the Pacific Indonesia LNG Company - Dames and Moore:::::: (Dames & Moore, 1974)
Pacific Indonesia LNG Company (Applicant) proposes to construct ship unloading, transfer, storage, and vaporization facilities at Port Hueneme and Oxnard, California, for the importation of liquefied natural gas (LNG). This report discusses importation at rates up to the equivalent of one billion cubic feet of natural gas per day. However, Applicant proposes to install facilities at this time capable of handling LNG purchased in Indonesia equivalent to 546 MMcfd. The gas will be used in the public utility gas system of Southern California Gas Company (SoCal), an affiliate which serves or supplies nearly all of Southern California. Imported LNG is needed to offset the decline in gas supplies from domestic sources in a region which for historical and economic reasons has become uniquely dependent upon natural gas for fuel.The proposed project is to provide facilities for unloading LNG ships, transfer of LNG to above-ground storage, vaporization, odorization, measurement, and delivery into the gas transmission system of SoCal for distribution to customers throughout Southern California.